Computing Hypercrossed Complex Pairings in Digital Images. (18th December 2013) - Öztunç, Simge; Mutlu, Ali; Bildik, Necdet
Abstract : We consider an additive group structure in digital images and introduce the commutator in digital images. Then we calculate the hypercrossed complex pairings which generates a normal subgroup in dimension 2 and in dimension 3 by using 8- adjacency and 26- adjacency .